The Relationship Between Social Media Addiction and Emotional Stability in Adolescents in Kupang City - Maria Selda Andriani Ngamo; Diana Aipipidely; Marylin S Junias; Juliana Marlin Y Benu (Universitas Nusa Cendana, 2023)
Indonesia is an Internet user, and digital media is currently the main choice of communication channel they use. One of the effects that occurs when using too much social media is that the emotions expressed through social media can be transmitted unconsciously. Emotions expressed through social media can be transmitted unnoticed by social media users when reading or viewing content from other users. The hypothesis in this study is that there is a relationship between social media addiction and emotional stability in adolescents in Kupang City. Participants in this study were teenagers aged 15-18 years who actively used social media in the city of Kupang, totaling 360 respondents. The analysis used is the correlation test. This study concludes that there is a negative and significant relationship between social media addiction and emotional stability in adolescents in Kupang City. It is shown from the results of the analysis that there is a correlation coefficient of -0.361 with a significant level of 0.000.